Problem-based learning to improve critical thinking in network topology material in grade X - Veri Nurkolis; Hary Suswanto; Syaifudin Ramadhani; Salma Huwaida Nisrina; Suti Mega Nur Azizah; Wafik Nur Muhammad Arwani; Wahyu Dwi Setyawan (Wiyata Dharma: Jurnal Penelitian dan Evaluasi Pendidikan, 2025)
This study aims to analyze the improvement of students' critical thinking skills through the application of the Problem-Based Learning (PBL) model in Network Topology material in class X at SMAN 4 Malang. The study used a quasi-experimental method with a pretest–posttest control group design. The sample consisted of 68 students divided into experimental and control groups. The instruments used included a concept comprehension test and an active participation questionnaire. The results showed that the experimental group, which learned using the PBL model, experienced a significant increase in concept comprehension and active participation compared to the control group. The PBL model proved to be capable of creating collaborative learning, increasing student activity, and strengthening critical thinking skills in network topology material. These findings confirm that PBL is an effective approach to enriching problem-solving-based learning processes in secondary schools.